Design tool chain for cyber-physical systems: lessons learned - Sztipanovits, Janos; Bapty, Ted; Neema, Sandeep; Koutsoukos, Xenofon; Jackson, Ethan (DAC '15 Proceedings of the 52nd Annual Design Automation Conference, 2015)
Design automation tools evolved to support the principle of "separation of concerns" to manage engineering complexity. Accordingly, we find tool suites that are vertically integrated with limited support (even intention) for horizontal integratability (i.e. integration across disciplinary boundaries). CPS challenges these established boundaries and with this - market conditions. The question is how to facilitate reorganization and create the foundation and technologies for composable CPS design tool chains that enables reuse of existing commercial and open source tools? In this paper we describe some of the lessons learned in the design and implementation of a design automation tool suite for complex cyber-physical systems (CPS) in the vehicle domain. The tool suite followed a model- and component-based design approach to match the significant increase in design productivity experienced in several narrowly focused homogeneous domains, such as signal processing, control and aspects of electronic design. The primary challenge in the undertaking was the tremendous heterogeneity of complex cyber-physical systems (CPS), where such as vehicles has not yet been achieved. This paper describes some of the challenges addressed and solution approaches to building a comprehensive design tool suite for complex CPS.